Design and realization of X-band wideband directional coupler using elliptical multilayer substrate architecture - Shilpa Ankit Rana; Ashish Kalubhai Sarvaiya (Bulletin of Electrical Engineering and Informatics, 2026)
This paper presents the design analysis and realization of a wideband directional coupler tailored for X-band microwave applications. Directional couplers are critical components in modern microwave systems, where wide bandwidth and compact size are essential. The proposed design employs a multilayer configuration using TLY-5 substrate (epsilon r=2.20 and tangent delta=0.003), with a thickness of 0.508 mm and 17 µm copper cladding. The coupler is designed and simulated using Ansys high frequency structure simulator (HFSS) and subsequently fabricated for performance validation. It achieves a coupling factor of 3.5±0.6 dB across the 7–14 GHz range, with a transmission loss of 2.9±0.5 dB. Both return loss and isolation consistently exceed 20 dB throughout the operational band. The design exhibits a fractional bandwidth (FBW) of 66.67%, confirming its broadband capability. With a compact footprint of 2.475 lambda g ×1.485 lambda g, the coupler offers reasonable impedance matching and broadband performance, making it well-suited for integration in microwave circuits, particularly in variable attenuators and wideband communication systems.